Demokrasi indonesia di persimpangan: harapan rakyat dan realitas politik - Naeda, Dila Olga (Maliki Interdisciplinary Journal, 2026)
Indonesian democracy was born from the nation’s struggle to achieve people’s sovereignty and freedom in state life. This article discusses the development of democracy in Indonesia, public expectations of democracy, political realities, and efforts to strengthen democracy so that it better serves the people. The results of the discussion show that Indonesian democracy has developed from the parliamentary era to the reform era, which is more open to public participation. However, democracy still faces various challenges such as corruption, money politics, domination of political elites, as well as the spread of hoaxes and polarization on social media. Therefore, political education, strict law enforcement, and increased public participation are needed to create a more just, transparent, and prosperous democracy.